Few-layer NbSe2@graphene heterostructures as anodes in lithium-ion half- and full-cell batteries - Quoc Hai Nguyen; Kim, Hyeongwoo; Kim, Il Tae; Choi, Wonchang; Hur, Jaehyun (ELSEVIER SCIENCE SA, 2020)
A few-layered NbSe2@graphene (FLNG) composite is synthesized via wet ball-milling (WBM) as a new promising anode (wet ball-milled NbSe2@graphene or WBMNG) in lithium-ion half- and full-cell batteries. In this study, we first demonstrate that few-layered graphene (FLG) with low defect density can be prepared from bulk graphite via ball-milling in ethanol. Extending this concept, NbSe2 is introduced as a new 2D additive in WBM to produce a well-defined FLNG composite. FLNG contains NbSe2 particles (similar to 200 nm lateral size and similar to 7.7 nm thickness (similar to 37 layers)) embedded on a larger FLG (similar to 1 mu m lateral size and similar to 1.7 nm thickness (similar to 5 layers)). The formation of FLNG is based on the solid lubrication in the WBM process that facilitates the exfoliation of 2D materials (NbSe2 and graphite), which leads to the increased surface area, enhanced electrical conductivity, and homogeneous mixing. When applied as an anode in a lithium-ion battery, FLNG (or WBMNG) exhibits excellent electrochemical performances in both WBMNG//Li half-cell and WBMNG//LiFePO4@graphite full-cell batteries. The half-cell displays a reversible discharge capacity as high as similar to 1000 mAh g(-1) (capacity retention of similar to 88% compared with the initial capacity) at 0.1 A g(-1) after 200 cycles and similar to 700 mAh g(-1) at 1 A g(-1) after 1000 cycles, with an excellent rate capability (similar to 76% capacity retention at 10 A g(-1) compared to the capacity at 0.1 A g(-1)). Moreover, the practical full-cell delivers a high energy density of similar to 216 Wh kg(-1) after 100 cycles with excellent rate capability.
Keywords: REDUCED GRAPHENE OXIDE; LI-STORAGE; TRIBOLOGICAL PROPERTIES; NANOCOMPOSITE ANODE; SCALABLE PRODUCTION; RAMAN-SPECTROSCOPY; HYBRID NANOSHEETS; PROMISING ANODE; PERFORMANCE; GRAPHITE